Effects of different levels of controlled hypotension on regional cerebral oxygen saturation and postoperative cognitive function in patients undergoing total knee arthroplasty - Zhao, Yajuan; Zang, Chuanbo; Ren, Shengjie; Fu, Jianbin; Liu, Ning; Zhou, Ziyu; Lang, Bao (Frontiers in Medicine, 2022)
Background: Controlled hypotension technique was usually used to reduce intraoperative bleeding , and it could improve visualization of the surgical field during total knee arthroplasty (TKA). However, inappropriate controlled hypotension , through reducing cerebral blood flow or cerebral perfusion pressure, may cause postoperative cognitive dysfunction, so it is important to identify the appropriate level of controlled hypotension. Objective: To investigate the effects of different levels of controlled hypotension on regional cerebral oxygen saturation and postoperative cognitive function in patients undergoing TKA. Methods: Patients meeting inclusion criteria were enrolled through preoperative visits and basic information was obtained. The patients were randomly divided into three groups: GroupA, MAP was maintained at 90%-100% of the baseline;Group B, MAP was maintained at 80% -90% of the baseline; Group C , MAP was maintained at 70%- 80% of the baseline. The MAP, HR and rSO2 were observed and recorded during the operation. The C-reactive protein(CRP), hemoglobin(Hb)and MMSE score at1st, 2nd and 3rd day after operation were recorded. SPSS25.0 was used for data analysis. Result: When the MAP had a decrease among the three groups, rSO2 did not decrease significantly, and none of the patients experienced POCD which was measured by MMSE. And there was no correlation between the decline in rSO2 and that in MAP. Conclusion : No POCD was experienced in the three groups, and we recommend that the controlled hypotensive target indicated by MAP was maintained at 70%- 80% of the baseline which not only decreases intraoperative bleeding and improve the quality of the surgical field, but also is still within safe levels.